Nasal nitric oxide in healthy adults - reference values and affecting factors - Antošová, M; Mokrá, Daniela; Tonhajzerová, Ingrid; Mikolka, Pavol; Kosutova, P; Mešťaník, Michal; Pepucha, L; Plevková, Jana; Buday, Tomáš; Čalkovský, Vladimír; Benčová, Alica (Physiological research, 2017)
Nitric oxide (NO) is an important endogenous mediator with significant role in the respiratory system. Many endogenous and exogenous factors influence the synthesis of NO and its level is significantly changed during the inflammation. Analysis of nasal nitric oxide (nNO) is not validated so far as the diagnostic method. There is a lack of reference values with possible identification of factors modulating the nNO levels. In healthy adult volunteers (n=141) we studied nasal NO values by NIOX MINO® (Aerocrine, Sweden) according to the recommendations of the ATS & ERS. Gender, age, height, body weight, waist-to-hip ratio, FEV1/FVC, PEF and numbers of leukocytes, eosinophils, basophils and monocytes were studied as potential variables influencing the levels of nNO. The complexity of the results allowed us to create a homogenous group for nasal NO monitoring and these data can be used further as the reference data for given variables. Because of significant correlation between nNO and exhaled NO, our results support the "one airway - one disease" concept. Reference values of nasal NO and emphasis of the individual parameters of tested young healthy population may serve as a starting point in the non-invasive monitoring of the upper airway inflammation.
Keywords: mužské pohlaví; respirační funkční testy; Male; Nasal Mucosa; Humans; Female; lidé; nosní sliznice; ženské pohlaví; oxid dusnatý; Respiratory Function Tests; mladiství; Reference Values; Young Adult; Adolescent; mladý dospělý; referenční hodnoty; Nitric Oxide; dospělí; Adult